KELUARGA BERWAWASAN EKOLOGIS - Rumampuk, Selvie (HOLISTIK, Journal Of Social and Culture, 2019)
The family is the basic cell of society as the formation of religious values and culture to every human being on which different though, learning to live together with others and to belong to each other. The family also became the starting point for building a "repent ecologically" that will grow and develop change and renewal of the attitudes and actions of living environmentally in building integrity to live together. The husband and wife relationship is the most important relationship in the family. The quality of the relationship that's very influential contribution to family life. Although the husband and wife are generally good, both are nonetheless difficult to achieve happiness when their relationship with children is compromised. Then for the sake of their happiness, its full husband and wife need a good relationship with their children. As is the case in the relationship between husband and wife, the relationship between parents and children also contains some facet i.e. in terms in terms of feelings, thoughts, and in terms of the will or a will. The integrity of shared life understood as a harmonious relation between human to human, human to human creation and nature with God the creator. Wholeness of life includes humans and the environment. Environmental functions buffer fairy life are especially important. Therefore, management and development is directed to maintain its presence in the dynamic balance to be utilized for the welfare of most live together. It is the responsibility of everyone, and this responsibility begins from and in the education of families.Keywords: relationship, integrity, harmonious